Tathwir wasilat al-kura al-mutaharika 'ala madaah al-adawat al-madrasiyah litalabat al-saff al-sabi' bil-madrasah al-thanawiyah Buwa Luwu - Mustafa, Mustafa; Nur Amalia Ilyas (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
Based on the observations made by the researcher, there are some obstacles that were found, including the lack of student interest and enthusiasm for learning the Arabic language, and some of them are still unable to read the alphabet. Therefore, the researcher took the title: Developing the Rolling Ball Tool for School Materials for Seventh Grade Students at Buwa Luwu High School. This research aims to develop the rolling ball tool for school materials for seventh grade students at Buwa Luwu High School. The researcher hopes that this research will be a solution that can be taken into consideration in the world of education, especially to increase students' understanding and enthusiasm for learning the Arabic language. This research uses the Research and Development (R&D) methodology using the ADDIE model, which consists of five stages: (1) Analysis phase, (2) Design phase, (3) Development phase, (4) Implementation phase, (5) Evaluation phase. The results of this development are: developing the rolling ball tool for school materials for seventh grade students at Buwa Luwu High School in learning the Arabic language and the level of validity of this research. The suitability of the tool conducted by the media expert is 84%, the suitability of the tool conducted by the subject expert is 92%, and the suitability of the tool conducted by the subject teacher is 95%. Considering the results of the auditor and the number of questionnaires conducted by the researcher, it can be concluded that the presentation of the results of this research is accurate by 19%. ملخص البحث بناءً على الملاحظات التي قامت بها الباحثة، هناك بعض العوائق التي تم العثور عليها، منها قلة الاهتمام الطلبة حماسهم لتعليم اللغة العربية، وبعضهم لا يزالون غير قادرين على قراءة الحروف الهجائية. ولذلك أخذت الباحثة عنوان: تطوير وسيلة الكرة المتحركة على مادة الأدوات المدرسية لطلبة الصف السابع بالمدرسة الثانوية بووا لووو. يهدف هذا البحث إلى تطوير وسيلة الكرة المتحركة على مادة الأدوات المدرسية لطلبة الصف السابع بالمدرسة الثانوية بووا لووو. تأمل الباحثة أن يكون هذا البحث حلاً يمكن أخذه بعين الاعتبار في عالم التعليم، خاصة من أجل زيادة الفهم الطلبة والحماسة في تعليم اللغة العربية. يستخدم هذا البحث منهج البحث والتطوير (R&D) باستخدام نموذج ADDIE الذي يتكون من خمس مراحل: (1) مرحلة التحليل، (2) مرحلة التصميم، (3) مرحلة التطوير، (4) مرحلة التنفيذ، (5) مرحلة التقييم. نتائج هذا التطوير هي: تطوير وسيلة الكرة المتحركة على مادة الأدوات المدرسية لطلبة الصف السابع بالمدرسة الثانوية بووا في تعلم اللغة العربية وما هو مستوى التحقق من صحة هذا البحث. ملاءمة الوسيلة التي أجراها خبير الوسيلة 84%، ملاءمة الوسيلة التي أجراها خبير المادة 92%، ملاءمة الوسيلة التي أجراها مدرسة المادة 95%. وبالنظر إلى نتائج المدقق وعدد الاستبيانات التي اجرائها الباحثة، يمكن استنتاج أن عرض نتائج هذا البحث صحيح بنسبة 19%. كلمات أساسية: التطوير، وسيلة الكرة المتحركة، المادة